Penerapan Pembelajaran STEAM (Science, Technology, Engineering, Arts, Mathematics) - Herliyanto, Muci (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to describe the implementation of STEAM (Science, Technology, Engineering, Arts, Mathematics) learning in elementary schools and its impact on student engagement and competencies. The research uses a qualitative approach with a case study design. The subjects of the study were classroom teachers and students in an elementary school, while the object was the implementation of STEAM-based learning. Data were collected through observation, interviews, and documentation. The data were analyzed using thematic analysis to identify significant patterns in STEAM implementation. The results show that the STEAM approach promotes more active, creative, and collaborative learning. Students demonstrate improved conceptual understanding, critical thinking, and problem-solving skills. Teachers also experienced growth in designing integrative learning strategies. In conclusion, STEAM learning is effectively implemented in elementary schools to enhance learning quality and 21st-century competencies.